Characteristics of Pseudomonas spp. causing grain discoloration and sheath rot of rice, and associated pseudomonas epiphytes - Zeigler, Robert S.; Álvarez, E. (Scientific Societies, 1990)
Ninety-five strains of fluorescent (presumed to be Pseudomonas spp.) and nonfluorescent pathogens of rice causing grain and sheath rot, dirty panicle, and manchado de grano, and 21 strains of nonpathogenic fluorescent pseudomonads isolated from rice grain and sheaths from 22 countries were compared with 26 reference strains (Pseudomonas avenae, P. fuscovaginae, P. glumae, P. marginalis, and P. syringae) with the use of morphology, serology and 77 physiological traits. A Ward’s minimum variance cluster analysis grouped the strains into seven clusters corresponding to six bacterial species: P. fuscovaginae (two clusters), P. avenae, P. fluorescens, P. glumae, P. putida, and P. syringae. Every strain from Chile that caused sheath and grain rot was P. syringae. The rest of the pathogenic fluorescent strains were consistent with P. fuscovaginae but were grouped into two different clusters, suggesting that further study of this pathogen is warranted. The nonfluorescent pathogens were either P. avenae or P. glumae, and no pathogenic Erwinia spp. were encountered. Approximately 25% of the strains of P. syringae and P. fuscovaginae agglutinated with their respective heterologous antisera, and up to 75% of P. avenae and P. glumae agglutinated with their respective antisera. There was less than 10% agglutination between fluorescent and nonfluorescent pathogens and their respective antisera. The nonpathogenic strains did not react with any antisera. It is concluded that four bacterial species causing grain or sheath rot of rice were encountered in this study. They are P. fuscovaginae, P. syringae pv. syringae, P. avenae, and P. glumae, with P. fuscovaginae and P. avenae the most common. These rice pathogens, formerly believed to be of limited distribution, are shown to be distributed worldwide.